Evaluation of spatio-temporal variations in water quality and suitability of an ecologically critical urban river employing water quality index and multivariate statistical approaches: A study on Shitalakhya river, Bangladesh. Issue 5 (12th November 2020) - Kabir, Md. Humayun; Tusher, Tanmoy Roy; Hossain, Md. Saddam; Islam, Md. Sirajul; Shammi, Rifat Shahid; Kormoker, Tapos; Proshad, Ram; Islam, Maksudul
Abstract: The aim of this study was to investigate the spatio-seasonal variations in water quality and suitability of the Shitalakhya river, an economically important and ecologically critical urban river in Bangladesh, along with associated influencing factors and possible sources of water pollution. Therefore, surface water samples were collected monthly from five sampling sites, and fourteen water quality parameters were evaluated. The results showed that some studied water quality parameters, e.g., temperature, TDS, TA, TH, NO2 –, and NO3 –, exceeded the maximum allowable limit, whereas statistically significant ( p < . 05) variations were observed among pre-monsoon (February–May), monsoon (June–September), and post-monsoon (October–January) seasons. The values of water quality index (WQI) exhibited that the water quality was found to be very poor to unsuitable for drinking, fisheries, or aquatic environment. The principal component analysis (PCA) extracted two PCs explaining 91.092% of the total variance, which suggested that the variations in water quality are attributed mainly to point and nonpoint sources of contamination including municipal and industrial wastewater discharge, and agricultural runoff of inorganic fertilizers. The cluster analysis (CA) also showed relative spatial and seasonal variations in river water quality, indicating the influence of hydrological changes and pollution sources. The study revealed that the water of the Shitalakhya river is highly polluted and potentially hazardous for human uses, and thus more attention should be given to safeguard such an important urban river.